OP90 Evaluating Mental Wellbeing in Children with Health Related Barriers to Learning: Results of a Quasi-Experimental before and after Intervention. (17th September 2012) - Putz, RE; Clarke, A
Abstract : Background: Clear associations have been demonstrated between poor mental health, behavioural problems and low educational attainment in secondary school children while negative self-perceptions are associated with truancy and classroom disruption at secondary school level. The majority of research in this field focuses and measures outcomes in terms of mental illness. Fewer interventions have been evaluated using positive mental health/mental wellbeing measures, though the body of evidence is growing. We aimed to evaluate the effect of targeted school counselling or 'Wellbeing Mentorship' on mental wellbeing in children with health related barriers to learning at risk of low educational attainment and attendance. Health related barriers to learning included medical issues, mental health, sexual health, bullying, family challenges and emotional and behavioural barriers. Methods: The Warwick Edinburgh Mental Wellbeing Scale (WEMWBS) was used to evaluate mental wellbeing in pupils seen by Wellbeing Mentors. WEMWBS is validated for use in populations aged 13+. Gender, age, school deprivation, attainment and attendance were measured. Mentors at eight diverse schools collected data from April 2011 to February 2012. A power analysis was conducted. Given the risk of high attrition, pupils were sampled within a designated time frame wherein Mentors evaluated every eligible pupil. Pupils completed WEMWBS at the beginning, end, and 6–10 weeks after their last mentoring session. Interventions comprised 6 sessions of weekly one-to-one health and wellbeing support. Results: Ninety-six eligible pupils undertook and completed WEMWBS, out of 160 estimated mentoring referrals. Using paired t-tests and ANOVA, we assessed changes in WEMWBS scores between time points. Pupils' mental wellbeing significantly improved (95% Confidence) from baseline to completion. Girls' baseline mean WEMWBS score (43.3) increased by 7.4 points to 50.7 at completion; boys baseline mean (44.2) increased by 6.2 to 50.4. These changes were sustained at follow up. Boys and girls results demonstrate statistically and clinically meaningful change. We compared our results with WEMWBS data collected in 2008 from two of the same and one similar school (n=753). The comparator mean for girls (47.4) and boys (49.8) indicate that mentored pupils improved their mental wellbeing to a similar level (boys) or a significantly higher level (girls). Cooperation, process measures, attainment and attendance reporting varied greatly between schools; these data are still being collected. Conclusion: Both before and after and population controls suggest that mentoring is a worthwhile intervention for improving mental wellbeing in secondary school pupils identified with health related barriers to learning.